International heritage law for communities : exclusion and re-imagination - Lixinski, Lucas (Oxford : Oxford University Press, 2019)
This text engages the shortcomings of the field of international heritage law, arguing that the five major UNESCO treaties have effectively prevented local communities from having a say in how their heritage is managed.
This edition also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 14, 2019).
Keywords: Historic sites -- Law and legislation; Cultural property -- Protection (International law); Unesco